War crimes against civilians and the contemporary point of view (A comparative study between Imamiyah jurisprudence laws and international laws - sayyed Hossen Altaha / Hossen Haydari / Ali Rahmah Ramada ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
This article discusses the war crime issue, since war crimes are considered extremely important. It is also a significant topic of discussions these days. The researcher aimed to explain the meaning of the term “war crimes” according to its presence in the sources of international humanitarian laws. In this regard with the emphasize on the idea and content about war crimes contained in the works of our prominent Imamiyah jurisprudents, it became evident that the term war crimes, is a modern term unfamiliar to the Imamiyah jurisprudents of the past, Therefore the current article defines the war crime within the framework of law as follows: Any act or omission , during war or armed conflict, committed by a member of one of the parties to the conflict, whether civilian or military, provided that this act or omission is directed against enemies people or their private or public property, and that carrying out these acts constitutes a legal prohibition according to the Imamiyah jurisprudence, and at the same time constitutes a violation of the laws and customs of war mentioned in the Hague Conventions of 1899 AD, 1907 AD, and the Four Geneva Convention of August 12, 1949 AD, and protocol modifications as well as all newly established protocols to date. Based on this definition, there is consensus among Imamiyah jurisprudents and the international humanitarian law regarding the prohibition of killing individuals who do not take part in war operations during the outbreak of war and conflict, including women, the elderly, children, clerics and workers in their workshops. They also concur that it is forbidden to demolish and ruin public and private properties that are not involved in war necessities. They prohibit mass killing and genocide and expelling people from the involved country as well; Because in terms of legal and Shariah laws, all these are considered war crimes, so committing them is not permissible. Furthermore, war crimes are among the forbidden sins according to Shari'ah. Therefore, not committing any war crimes, bring a Muslim closer to God. The present study also investigated how Imamiyah jurisprudence differs from the jurisprudence of other countries in regard to the purposes of war. And it became evident that the annihilation of humanity is not one of the goals of the Holy Shari'ah; Rather, Imamiyyah jurisprudence considers the war as an emergency that must be ended with the least amount of damage and the least amount of time feasible; Because the desire for dominance and the instinct of revenge and looting the riches of the world and the desire to gain power over others are never considered as the goals of a fair war. What Jihad legalized is that there is nothing but elevating the word of God. Highlighting the fact that the origin and capital of the divine call are humans themselves; as a result, if humans disappear, there will be no divine call.